Evaluación de la viabilidad de bio formulaciones a base de PGPRs y sus efectos en plantaciones de Theobroma cacao L. CCN51 - García Gallirgos, Víctor Jorge (2021)
The present research evaluates the study of five bacterial strains or PGPRs, these strains live in association with plants generating a symbiosis, growth and protection of the same, the strains used are Pseudomonas protegens CHA0, Serratia marcenses 3/8, Acinetobacter calcoaceticus BM2/12 P. veronii R4 and Enterobacter asburiae 3/14, all obtained from the strains of the Biotechnology Laboratory of the UTEQ, with the objective of determining the viability of bio formulations based on PGPRs and their effects on plantations of Theobroma cacao L. CCN51. The viability of the bacterial strains was evaluated by placing them in the culture media established in the research, subsequently determining the CFU/ml of medium up to 26 days. Quinolytic activity, chitin degradation, urease production, potassium and phosphate solubilization were also evaluated. The presence of the ChiA gene was determined by PCR with specific primers. Field trials were carried out at "Ignolia" farm, Cotopaxi, La Maná, El Moral. The trials on T. cacao CCN51 consisted of different forms of application of bacterial consortia at 20%. The treatments under study were: foliar, injection, edaphic, chemical and control. A DCA was used to evaluate the viability of the rhizobacteria and BCA was used for agronomic performance. Strains 3/8, BM2/12, R4 and 3/14 presented the ChiA gene, within the tests for chitin degradation, 3/8 and BM2/12 have a higher catalytic domain in degradation. In the solubilization of minerals (N, P, K) it was determined that BM2/12 has the capacity to solubilize phosphorus and potassium, CHA0 solubilizes a high content of nitrogen and phosphorus in contrast to the other strains. The application of these formulations reduced the incidence of Moniliophtora roreri, Phytophthora spp and Cherelle wilt, which indicates that these formulations can be considered as an alternative for their management and control. The agronomic and yield variables showed a greater increase with 25.2 floral cushions, 107.9 foliar emissions, 1270.63 kg in yield compared to the control with 20.3 floral cushions, 83.7 foliar emissions and a yield of 473 kg. Key words: Rhizobacteria, biocontrol, mineral solubilization, viability.